The Effectiveness of the Dual System Education Program at Vocational High Schools in Sidoarjo Regency: Efektivitas Program Pendidikan Sistem Ganda di Sekolah Menengah Kejuruan Kabupaten Sidoarjo - Rahmawati, Reni; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to analyze and describe the effectiveness of the Dual System Education Program effectiveness at SMK Negeri 01 Buduran, to analyze and describe the factors that become obstacles in implementing the effectiveness of the Dual Education Program at SMK Negeri 01 Buduran. This research method uses descriptive qualitative. This research was conducted at SMK Negeri 01 Buduran which is located at Jl. Jenggolo No.1B, Bedrek, Siwalanpanji, Kec. Buduran, Sidoarjo Regency, East Java 61252. Data collection was carried out by in-depth interviews, observation and review of relevant literature. The technique of determining the informants used purposive sampling. The informants in this study were the school itself, in other words the Principal of SMK Negeri 01 Buduran and the accompanying teacher of the PSG Program who were the main informants as the main person in charge of the Dual System Education Program at SMK Negeri 01 Buduran. The analysis technique in this study is a qualitative analysis type, referring to the theory of Miles and Huberman. The results show that the effectiveness of the Dual System Education Program at SMK Negeri 01 Buduran includes achieving the goals or results of the Dual System Education Program at SMK Negeri 01 Buduran is still not optimal because it is fluctuating when viewed from the absorption rate of graduation in DU/DI. Obstacles In implementing the effectiveness of the Dual System Education Program at SMK Negeri 01 Buduran the limitations of finding a representative DUDI, not all DUDI provide jobs/training to PSG students according to the competencies expected by the school and the character of students who are different from one another also plays a role in determining student ethics on the implementation of PSG.